LEMBAR KEGIATAN SISWA MODEL LEARNING CYCLE 7E MATERI PEMANASAN GLOBAL UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Lika Mariya; Agus Suyatna (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Global warming is a complex problem. In the global warming material, students are expected to analyze the phenomenon of global warming, the greenhouse effect and climate change and their impact on life and the environment. In addition, students are also required to be able to bring up the idea of ​​solving the symptoms of global warming and its impact on life and the environment. To overcome the effects of global warming, the necessary critical thinking skills of students using the corresponding worksheets. The purpose of this study is to develop a global warming worksheets that can foster students' critical thinking skills. The method used by the R & D stage of development following the model of the 4-D by Thiagarajan and Sammel (1974). This model consists of four stages of development, ie define, design, develop, and disseminate. In this article, the study was limited to the design phase. Results of the study concluded LKS to foster critical thinking skills of students on global warming material has a systematic learning model 7E learning cycle with the stages Elicit (raises an initial understanding of students), Engagement (involved), Exploration (investigate), Explanation (explain), Elaboration ( outlines), Evaluation (judge), and Extend (expand). Keywords: Worksheet, Learning Cycle 7E, critical thinking.